New and little-known species of Arachnospila (subgenus Ammosphex) (Hymenoptera: Pompilidae) from East Siberia - Loktionov, Valery M.; Lelej, Arkady S. (Zootaxa, 2015)
Seventeen species are listed. Five new species: Arachnospila (Ammosphex) kasparyani sp. nov. (Tuva), A. (A.) maxim sp. nov. (Tuva, Khakassia), A. (A.) moczari sp. nov. (Tuva), A. (A.) scythia sp. nov. (Tuva), A. (A.) sibirica sp. nov. (Tuva, Republic of Altai) are described and illustrated. Arachnospila (Ammosphex) eoabnormis Lelej, 1995, A. (A.) orientausa Loktionov & Lelej, 2011, and A. (A.) mongolopinata Wolf, 1981 are newly recorded from East Siberia. The distribution of eight species in East Siberia is enlarged. The revised key of 24 species in males from East Siberia and Russian Far East is given.